δ-Ctenitoxin-Pn1a, a Peptide from Phoneutria nigriventer Spider Venom, Shows Antinociceptive Effect Involving Opioid and Cannabinoid Systems, in Rats - Bruna Luiza Emerich; Renata C. M. Ferreira; Marta N. Cordeiro; Márcia Helena Borges; Adriano M. C. Pimenta; Suely G. Figueiredo; Igor Dimitri G. Duarte; Maria Elena de Lima (Toxins, 2016)
PnTx4(6-1), henceforth renamed δ-Ctenitoxin-Pn1a (δ-CNTX-Pn1a), a peptide from Phoneutria nigriventer spider venom, initially described as an insect toxin, binds to site 3 of sodium channels in nerve cord synaptosomes and slows down sodium current inactivation in isolated axons in cockroaches (Periplaneta americana). δ-CNTX-Pn1a does not cause any apparent toxicity to mice, when intracerebroventricularly injected (30 μg). In this study, we evaluated the antinociceptive effect of δ-CNTX-Pn1a in three animal pain models and investigated its mechanism of action in acute pain. In the inflammatory pain model, induced by carrageenan, δ-CNTX-Pn1a restored the nociceptive threshold of rats, when intraplantarly injected, 2 h and 30 min after carrageenan administration. Concerning the neuropathic pain model, δ-CNTX-Pn1a, when intrathecally administered, reversed the hyperalgesia evoked by sciatic nerve constriction. In the acute pain model, induced by prostaglandin E2, intrathecal administration of δ-CNTX-Pn1a caused a dose-dependent antinociceptive effect. Using antagonists of the receptors, we showed that the antinociceptive effect of δ-CNTX-Pn1a involves both the cannabinoid system, through CB1 receptors, and the opioid system, through μ and δ receptors. Our data show, for the first time, that δ-Ctenitoxin-Pn1a is able to induce antinociception in inflammatory, neuropathic and acute pain models.